2012
DOI: 10.1177/1045389x12438628
|View full text |Cite
|
Sign up to set email alerts
|

Reliable, high-frequency miniature valves for smart material electrohydraulic actuators

Abstract: A key element in developing high-performance smart material electrohydraulic actuators is the design of improved check valves for high-frequency fluid rectification. One method to create valves with fast frequency response is to replace the single-reed valves typically used in these systems with an array of miniature-reed valves. A robust miniature-reed design is presented to overcome the fatigue and fabrication limitations observed in previous approaches. The fluid–structure interaction between an individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…17 The third peak measured at 950 Hz is due to dynamics of the inlet (low-pressure) side of the system and does not appear in tests with the valves installed.…”
Section: No-reed Blocked Testingmentioning
confidence: 98%
See 1 more Smart Citation
“…17 The third peak measured at 950 Hz is due to dynamics of the inlet (low-pressure) side of the system and does not appear in tests with the valves installed.…”
Section: No-reed Blocked Testingmentioning
confidence: 98%
“…[13][14][15][16] Recent work by the authors demonstrated that the miniature valve approach can successfully rectify flow; however, the overall actuator bandwidth remains limited by the pump manifold design. 17 We investigate the effect of the fluid passages in the pumping manifold on the overall bandwidth of the actuator. A model for the fluid passages in the pump is developed and validated against experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…These single reed-type valves enabled increased performance up to several hundred hertz. In order to expand the performance into the kilohertz range, miniature check valves have been developed [12][13][14][15]. Smaller valves are designed with less mass to increase the frequency response, with multiple valves arranged in an array to decrease flow resistance losses.…”
Section: Smasis2012-8253mentioning
confidence: 99%
“…Smaller valves are designed with less mass to increase the frequency response, with multiple valves arranged in an array to decrease flow resistance losses. While miniature reeds have been shown to successfully rectify fluid flow, their impact on the overall performance of the system was limited due to the limited bandwidth of the fluid system, which includes the pumping chamber, output cylinder, and connecting passages [15].…”
Section: Smasis2012-8253mentioning
confidence: 99%
“…When the pump discharges liquid, the hysteresis of opening the outlet valve reduces the amount of liquid discharged from the pump chamber, and the hysteresis of closing the inlet valve makes the liquid in the pump chamber return to the inlet pipe again. Researchers have been committed to designing valves with high-frequency response to solve this problem [ 12 , 13 , 14 , 15 , 16 ]. The existing research in this field has become mature, and the response frequency of some high-frequency valves reachs over 1 kHz.…”
Section: Introductionmentioning
confidence: 99%